Download presentation
Presentation is loading. Please wait.
Published byMargery Harris Modified over 9 years ago
1
Part 2
2
Review… Solve the following system by elimination: x + 2y = 1 5x – 4y = -23 (2)x + (2)2y = 2(1) 2x + 4y = 2 5x – 4y = -23 7x = -21 x = -3 x + 2y = 1 -3 + 2y = 1 2y = 4 y = 2 (-3, 2)
3
What do you think you should do to solve this system? 4x + 5y = 7 6x – 2y = -18 (2)4x + (2)5y = (2)7 8x + 10y = 14 (5)6x – (5)2y= (5)-18 30x – 10y = -90 Can you multiply one of the equations to eliminate a variable? We will need to multiply BOTH equations to eliminate one of the variables. Since the “y” has opposite signs, what can we multiply the 1 st equation by and what can we multiply the 2 nd equation by to eliminate the “y”s? We can multiply the 1 st equation by 2 so it will become “10y.” We can multiply the 2 nd equation by 5 so it will become “-10y.”
4
8x + 10y = 14 30x – 10y = -90 38x = - 76 x = -2 4x + 5y = 7 4(-2) + 5y = 7 -8 + 5y = 7 5y = 15 y = 3 Now we have the system set up so we can solve it. Solve the system by adding. Now substitute “-2” into one of the ORIGINAL equations and solve for “y.” The solution to the system is (-2, 3).
5
3x + 2y = 10 2x + 5y = 3 (2)3x + (2)2y = (2)10 (-3)2x + (-3)5y = (-3)3 6x + 4y = 20 -6x – 15y = -9 -11y = 11 y = -1 Solve the following system by elimination. What do we need to multiply each equation by in order to eliminate one of the variables? Let’s eliminate the “x” variable. Multiply the 1 st equation by 2 to get “6x.” Multiply the 2 nd equation by -3 to get “-6x.” Remember, the signs will need to have opposite values. 3x + 2y = 10 3x + 2(-1) = 10 3x – 2 = 10 3x = 12 x = 4 The solution to the system is (4, -1).
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.